Is Ethnobotany and Ecological Science? Steps towards a complex Ethnobotany - Hurrell, Julio Alberto (2012)
There are different links between ecology and ethnobotany. In principle, because they have some common interests, like the conservation of plant resources. Nevertheless, the consolidation of the ecology as a science of synthesis that is based on the complexity of relationships between organisms and their surroundings, allows the ecology to provide a conceptual framework for more complex and comprehensive ethnobotany. This is also, for origin, a science of synthesis. In this contribution we discuss the basic aspects of ecology that can become guides for a complex framework of ethnobotany, which acts as a context in which their contributions to acquire significance. It also discusses various aspects of ethnobotany which, by its own complexity, are linked to the theoretical framework of ecology. Finally, we consider ethnobotany as an ecological science, from which certain assumptions are given, that can guide investigations based on the complex relationships between people and plants, the object of study of this science.